Big data and data science: what should we teach?. Issue 4 (9th October 2015) - Song, Il‐Yeol; Zhu, Yongjun
Abstract: The era of big data has arrived. Big data bring us the data‐driven paradigm and enlighten us to challenge new classes of problems we were not able to solve in the past. We are beginning to see the impacts of big data in every aspect of our lives and society. We need a science that can address these big data problems. Data science is a new emerging discipline that was termed to address challenges that we are facing and going to face in the big data era. Thus, education in data science is the key to success, and we need concrete strategies and approaches to better educate future data scientists. In this paper, we discuss general concepts on big data, data science, and data scientists and show the results of an extensive survey on current data science education in United States. Finally, we propose various approaches that data science education should aim to accomplish.